1994
DOI: 10.1111/j.1471-6712.1994.tb00013.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental Participation in the Care of Hospitalized Children

Abstract: The purpose of this study was to investigate those parts of the care of hospitalized children that their parents perform, the nursing tasks the parents themselves felt they could manage and whether parents' and staff members' opinions coincided. A questionnaire was given to parents of children between one week and five years of age who were hospitalized at a pediatric surgical department during a 6-week period (n = 40), a similar questionnaire being distributed to all the staff (n = 44). The results indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
4

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 14 publications
3
35
0
4
Order By: Relevance
“…More experienced nurses who feel secure in their profession are more able and willing to negotiate than less experienced nurses. 53 During a medical examination, the physician and the parents usually take the initiative in terms of conversation, but rarely the child. The physician directs most of his or her comments to the parents, while the child is addressed mainly during the physical examination.…”
Section: Roles and Partnershipmentioning
confidence: 99%
“…More experienced nurses who feel secure in their profession are more able and willing to negotiate than less experienced nurses. 53 During a medical examination, the physician and the parents usually take the initiative in terms of conversation, but rarely the child. The physician directs most of his or her comments to the parents, while the child is addressed mainly during the physical examination.…”
Section: Roles and Partnershipmentioning
confidence: 99%
“…Parents' interest in participating in technical aspects of care varied. For example, with regard to dressing changes, Kristensson-Hallstrom and Elander (1994) reported that 15% of parents did this procedure while 62% felt they could have done it. Webb et al(1985) found that 43% of parents either did or felt they could do a dressing change, while Hill identified that 38% of mothers wanted to do this care.…”
Section: Parents' Care Activitiesmentioning
confidence: 99%
“…Several researchers have used checklists of child care activities to identify activities parents participate in or in which they would like to participate (Algren, 1985;Blower, & Morgan, 2000;Hill, 1978;Jackson, Bradham, & Burwell, 1978;Kristensson-Hallstrom, & Elander, 1994;Merrow, & Johnson, 1968;Webb, Hull, & Madeley, 1985).…”
Section: Parents' Care Activitiesmentioning
confidence: 99%
See 2 more Smart Citations